The ERK-MNK-eIF4F signaling pathway mediates TPDHT-induced A549 cell death in vitro and in vivo. (March 2020) - Guo, Chuanlong; Hou, Yuzhen; Yu, Xuemin; Zhang, Fan; Wu, Xiaochen; Wu, Xianggen; Wang, Lijun
Abstract: The eIF4E/eIF4G complex plays a central role in gene expression regulation during the initial stage of translation. This study aimed to determine if the novel small molecule compound, TPDHT, could disrupt the interaction of eIF4E/eIF4G, and if it could exhibit excellent antitumor activity in vivo without causing apparent toxicity effect. This study investigated the antitumor mechanism of TPDHT in vitro and in vivo . TPDHT showed significant anti-proliferative activity on human lung cancer A549 cells, and it induced G0/G1 cycle arrest. Moreover, TPDHT also induced A549 cell apoptosis through the mitochondria-mediated apoptotic pathway. Our results indicate that TPDHT could disrupt the interaction of eIF4E/eIF4G, and the activity of eIF4F plays an important role in TPDHT-induced cell proliferation inhibition and apoptosis. Further research showed that TPDHT could inhibit the Ras/ERK/MNK pathway, and activation of the ERK pathway reversed TPDHT-induced cell proliferation inhibition and apoptosis. Taken together, our study findings indicated that TPDHT exerts an antitumor effect through an intrinsic apoptotic pathway controlled by the ERK/MNK/eIF4F pathway. Graphical abstract: Image 1 Highlights: TPDHT disrupts eIF4E/eIF4G interaction. TPDHT exhibits anticancer activity in vitro and in vivo . TPDHT induces apoptosis and cell cycle arrest by targeting ERK/MNK/eIF4F.